MODEL PERMINTAAN UANG DI INDONESIA DENGAN PENDEKATAN VECTOR ERROR CORRECTION MODEL - Mukhlis, Imam (Universitas Negeri Medan, 2016)
This research aims to estimate the demand for money model in Indonesia for 2005.22015.12. The variables used in this research are demand for money, interest rate, inflation, and exchange rate (IDR/US). The stationary test with ADF used to test unit root in the data. Cointegration test applied to estimate the long run relationship between variables. This research employed the Vector Error Correction Model (VECM) to estimate the money demand model in Indonesia. The results showed that all the data was stationer at the difference level (1%). There were long run relationship between interest rate, inflation and exchange rate to demand for money in Indonesia. The VECM model could not explain interaction between explanatory variables to independent variables. In the short run, there were not relationship between interest rate, inflation and exchange rate to demand for money in Indonesia for 2005.2-2015.12.